2021
DOI: 10.1080/19490976.2021.1966263
|View full text |Cite
|
Sign up to set email alerts
|

Deprivation of dietary fiber in specific-pathogen-free mice promotes susceptibility to the intestinal mucosal pathogen Citrobacter rodentium

Abstract: The change of dietary habits in Western societies, including reduced consumption of fiber, is linked to alterations in gut microbial ecology. Nevertheless, mechanistic connections between diet-induced microbiota changes that affect colonization resistance and enteric pathogen susceptibility are still emerging. We sought to investigate how a diet devoid of soluble plant fibers impacts the structure and function of a conventional gut microbiota in specific-pathogen-free (SPF) mice and how such changes alter susc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 52 publications
6
51
0
Order By: Relevance
“…In line with previous ndings 14,15,17 , the FF-fed mice exhibited a two-fold reduction in the colonic mucus layer thickness (Fig. 1b-d, Extended Data Fig.…”
Section: Microbiota-mediated Mucus Layer Thinning Is Associated With ...supporting
confidence: 91%
See 1 more Smart Citation
“…In line with previous ndings 14,15,17 , the FF-fed mice exhibited a two-fold reduction in the colonic mucus layer thickness (Fig. 1b-d, Extended Data Fig.…”
Section: Microbiota-mediated Mucus Layer Thinning Is Associated With ...supporting
confidence: 91%
“…Diet is an important environmental factor that affects the mucus barrier through the microbiota because: 1) dietary ber deprivation increases deterioration of the colonic mucus layer by mucolytic gut bacteria 14,15 ; and 2) Western-style diet increases the permeability of the colonic mucus layer 16 . The ber-deprived microbiota-mediated mucus barrier dysfunction re ects in enhanced susceptibility to infection by Citrobacter rodentium, a pathogen that must cross the mucus layer to reach the gut epithelium and initiate mucosal infection 14,17 . Nevertheless, little is known about how the diet-mediated mucus barrier dysfunction together with increased activities of speci c mucolytic microbes might impact oral tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly, they only seem to favor even more fermentation activities (e.g., fermentation gases). Lastly, since previous studies have elegantly shown in mice that dietary fiber intakes limited pathogen infection by protecting the mucus layer from degradation [ 36 , 142 , 143 ], we measured the total weight of mucin beads at the end of batch experiments. However, this previous hypothesis was not confirmed here, probably because of the use of simple batch experiments, which did not include goblet cells or allow the continuous supply of fiber sources or a renewal of luminal content.…”
Section: Discussionmentioning
confidence: 99%
“…There is a great body of evidence on the impact of diet on microbial gut health and how it can influence the course of a disease. In vivo studies where rodents were fed a fibre deprived diet saw rapid shifts in microbial gut populations (Schroeder et al 2018;Desai et al 2016;Neumann et al 2021;Riva et al 2019). Accordingly our data showed decreased diversity, increased Firmicutes/Bacteriodetes ratios and altered abundance of many taxa.…”
Section: Discussionmentioning
confidence: 99%